Fractional Hold Circuits for the Design of Positive - Sen, M. de la (2007)
The appropriate use of fractional order holds ( b-FROH) of correcting gains b2 [-1,1] as an alternative to the classical zero and first order -holds (respectively, ZOH, FOH) is discussed related to the positive realness of the associate discrete transfer functions obtained from a given continuous transfer function. It is proved that the minimum direct input-output gain (i.e. the quotient of the leading coefficients of the numerator and denominator of the transfer function) needed for discrete positive realness may be reduced by the choice of b compared to that required for discretization via a ZOH.